Feminisasi Kemiskinan dan Pendidikan di Aceh Besar - Musdawati, Musdawati (Intelektualita, 2024)
The feminization of poverty in Aceh Besar is a complex phenomenon in which women experience the impacts of poverty that are much more severe than men, although it is often not detected in statistical data. This study aims to identify the causes and impacts of poverty among women, with a focus on gender constructions that always position women in a vulnerable state. Although official poverty figures are often calculated based on male groups, women's experiences show that they bear a greater burden, both in terms of domestic responsibilities and in access to resources. Using a qualitative approach, this study collected data from in-depth interviews and focus group discussions with women in Aceh Besar, to explore their experiences related to education and poverty. The results show that education plays a key role in women's empowerment, as well as a tool for reducing poverty. Therefore, an emphasis on women's education and gender-based policies are crucial as solutions in addressing the feminization of poverty. This study suggests the need for more accurate and inclusive data to understand the dimensions of poverty faced by women and to formulate policies that are responsive to their specific needs